Prospecção e monitoramento informacional no contexto da inteligência competitiva em microempresas do ramo óptico da região de Marília - SP - Pacheco, Cíntia Gomes [UNESP] (2010)
The contemporary global scenario significantly affects all segments of the society, particularly business. In this context, small-sized business noteworthy because they are responsible for the economy in a particular city or region and, therefore, becomes relevant their research because of its entrepreneurial character. However, few studies are implemented under the small-sized business aspects in terms of business competitiveness and the use of strategic information for decision making. Moreover, companies generally unaware of the methods, techniques and information and communication technologies (ICTs) to perform activities of information scanning and information mining, which enables to identify and track information, allowing decisionmaking more assertive with use of strategic information, which contributes to business competitiveness. This work aimed to analyze the formal and informal methods of information scanning and information mining, through a structured interview applied to small-sized business in the optical sector associated with the Associação Comercial e Industrial de Marília (ACIM) belonging to the Núcleo Especializado de Ópticas de Marília (NEOM). It had to be based on an information scanning and information mining model, as well as aspects related to information behavior that allowed us to understand how companies deal with information in their business, as well as issues relating to the future of companies, through the perception of future scenarios. The data analysis was performed using the method 'Content Analysis'. The results were presented in detail by analysis category and also synthetically by companies, in order to provide this latter case the profile of each NEOM company. We identified the key information needs and information sources used by managers, given its informal practice in scanning and mining... (Complete abstract click electronic access below)